2006
DOI: 10.1152/ajprenal.00352.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphatidylinositol 3-kinase stimulates activity of the small-conductance K channel in the CCD

Abstract: We used Western blotting to examine the expression of phosphatidylinositol 3-kinase (PI3K) in the renal cortex and outer medulla and employed the patch-clamp technique to study the effect of PI3K on the ROMK-like small-conductance K (SK) channels in the cortical collecting duct (CCD). Low K intake increased the expression of the 110-kDa ␣-subunit (p110␣) of PI3K compared with rats on a normal-K diet. Because low K intake increases superoxide levels (2), the possibility that increases in superoxide anions may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…As reported previously for this preparation (33), inhibition of PI3-K increased the activity of this channel (data not shown).…”
Section: Tight Spatiotemporal Coupling Between Pi3-k Signaling and Ensupporting
confidence: 89%
“…As reported previously for this preparation (33), inhibition of PI3-K increased the activity of this channel (data not shown).…”
Section: Tight Spatiotemporal Coupling Between Pi3-k Signaling and Ensupporting
confidence: 89%
“…Thus the PI3K-induced depletion of PIP 2 might tend to reduce channel activity. Li et al (14) reported that inhibition of PI3K stimulated ROMK-like K ϩ channel activity in rat cortical collecting duct. In contrast, PI3K inhibitors reduced channel activity in cultured human proximal tubule cells.…”
Section: Discussionmentioning
confidence: 99%
“…P2Y 2 receptor Ϫ/Ϫ mice have been described previously (30). Likewise, isolation of collecting ducts suitable for electrophysiology has been described (29,31,32). In brief, mice were sacrificed by cervical dislocation and the kidneys immediately removed.…”
Section: Methodsmentioning
confidence: 99%